Effects of Climatic Factors on The Incidence Rate of Dengue Virus Infection in Surabaya During 2010-2013 - Winni Aprillia Putri; Abu Rohiman; Sulistiawati Sulistiawati; Dwiyanti Puspitasari (Biomolecular and Health Science Journal, 2019)
Introduction: Dengue Virus Infection (DVI) is one of cautious mosquito-borne virus disease that transmitted by Aedes aegypti and Aedes albopictus. Surabaya has the highest incidence rate of DVI in East Java. Transmission of dengue virus were significantly affected by the change of climatic factor components (precipitation, temperature, and humidity). This study is aimed to analyze the correlation between climatic factor components with the incidence rate of DVI in Surabaya and its distribution.Methods: This is a cross-sectional study using analytic observational approach. The Incidence rate of DVI during 2010-2013 datas were taken from Surabaya Health Office. Climatic factor datas on the same years were taken from Juanda Meteorological Station. Correlation tests were performed by using Spearman Test.Results: As the result, there were 7,685 DVI patients during 2010-2013. Male patients have less proportion (51.89%). The highest DVI cases are from the age group of 5-14 years (>40%). Incidence rate of DVI was increased during February to April, and highest incidence rate occured in 2010 (n=3,379). There were significant correlation between precipitation (r=0.419, p-value p=0.003) and humidity (r=0.502, p-value=0.000) with the incidence rate of DVI in Surabaya during 2010-2013.Conclusion: Therefore, precipitation and humidity are two climatic factor components that may effect the incidence rate of DVI in Surabaya.